Tinjauan Yuridis Penyalahgunaan Wewenang Aparat Dalam Penanganan Kasus Narkotika - Salsabila Salsabila; Budi Rizky Husin; Fristia Berdian Tamza; Muhammad Farid; Sri Riski (Indo Publishing, 2026)
Abuse of power by law enforcement officers in handling drug cases is a serious problem affecting the integrity of the criminal justice system in Indonesia. Actions such as fabricated cases, extortion, destruction of evidence, and negotiation of sentences frequently appear in various court reports and decisions, fueling public distrust in law enforcement agencies. This article aims to analyze various forms of abuse of power by officers in handling drug cases and the structural factors that trigger these violations, such as weak internal oversight, organizational culture, and regulatory deficiencies. The research method applied is a normative legal approach, encompassing an analysis of laws and regulations, court decisions, and relevant literature. The analysis shows that abuse of power occurs due to a lack of firmness in administrative and legal sanctions against officers, a dysfunctional external oversight mechanism, and the potential for conflicts of interest during the investigation process. This article recommends the need to strengthen accountability mechanisms, improve institutions, and implement stricter sanctions to reduce misconduct by officers in handling drug cases.